A formação de construções resultativas no português brasileiro - Núbia Rech (Cadernos de Estudos Lingüísticos, 2011)
This paper aims mainly at investigating if there is the formation of resultative constructions with simple adjective in Brazilian Portuguese, since researchers disagree on the existence of these constructions in Romance Languages. To start this discussion, first I make a distinction between resultative, depictive and circumstantial constructions. Then, I relate some of their main characteristics, testing how they appear in sentences written in Brazilian Portuguese. Afterwards, I propose an extension of Folli and Ramchand (2001)’s analysis on the Portuguese. These authors use a structure of verb phrase that consists of three different projections, each one consisting in a subpart of the event: Cause, Process and Result. My hypothesis about the Brazilian Portuguese is that the verbs of causative alternation – as they imply change of state – are the head of Result projection and have as their complement an adjective small clause (SC), whose predicate indicates the telic aspect of event, forming a resultative construction. Following this perspective of analysis, I study the possibility of formation of adjective resultatives with atelic and telic verbs that admit causative alternation. I also approach – although briefly – other types of constructions that express results, whose secondary predicates are, respectively, a complex adjective phrase, a PP or a DP. In this paper, only the constructions resulting from verbal actions are considered. Thus, goal of motion constructions – in which prepositions indicate the following of movement and its ending – and resultative constructions with causative verbs are not considered. The results show that there are not resultative constructions in the Brazilian Portuguese equivalent to those found in Germanic Languages, in which an atelic verb becomes a telic verb by adding a resultative secondary predicate to the sentence.